Capturing Geological Uncertainty in Salt Cavern Developments for Hydrogen Storage - Hector G. Barnett; Mark Thomas Ireland; Cees Van Der Land (Earth Science, Systems and Society)
Future energy systems with a greater share of renewable energy will require long-duration energy storage (LDES) to optimise the integration of renewable sources and hydrogen is one energy vector that could be utilised for this. Grid-scale underground storage of natural gas (methane) is already in operation in solution-mined salt caverns, where individual cavern capacities are ∼0.025–0.275 TWh. While salt caverns have traditionally been restricted to being developed onshore, in some offshore locations, such as the UK Continental Shelf, there are extensive evaporites that have the potential for storage development. Capacity estimates for offshore areas typically rely on generalised regional geological interpretations; they frequently do not incorporate site-specific structural and lithological heterogeneities, they use static cavern geometries and may use methodologies that are deterministic and not repeatable. We have developed a stochastic method for identifying potential salt cavern locations and estimating conceptual cluster storage capacity. The workflow incorporates principle geomechanical constraints on cavern development, captures limitations from internal evaporite heterogeneities, and uses the ideal gas law to calculate the volumetric capacity. The workflow accommodates either fixed cavern geometries or geometries that vary depending on the thickness of the salt. By using a stochastic method, we quantify the uncertainties in storage capacity estimates and cavern placement over defined regions of interest. The workflow is easily adaptable allowing users to consider multiple geological models or to evaluate the impact of interpretations at varying resolutions. In this work, we illustrate the workflow for four areas and geological models in the UK’s Southern North Sea: 1) Basin Scale (58,900 km2) - >48,800 TWh of hydrogen storage with >199,000 cavern locations. 2) Sub-Regional Scale (24,800 km2) - >9,600 TWh of hydrogen storage with >36,000 cavern locations. 3) Block Specific–Salt Wall (79.8 km2) - >580 TWh of hydrogen storage with >400 cavern locations. 4) Block Specific–Layered Evaporite (225 km2) - >263 TWh of hydrogen storage with >500 cavern locations. Our workflow enables reproducible and replicable assessments of site screening and storage capacity estimates. A workflow built around these ideals allows for fully transparent results. We compared our results against other similar studies in the literature and found that often highly cited papers have inappropriate methodologies and hence capacities.